OUTCOMES FOLLOWING OPEN BILIARY BYPASS FOR BENIGN BILIARY AND PANCREATIC DISEASES. (8th June 2013) - McCartan, D; Dasari, B; Ahmad, J; Jones, C; McKie, L; Taylor, M A; Diamond, T
Abstract : Aims/Background: The aim of this study was to evaluate the outcomes following open biliary bypass for benign biliary and pancreatic diseases. Method: Sixty-four patients (M: F=34:30) aged 15 to 89 years (median age: 54 years) underwent biliary bypass for benign diseases between 2001 and 2011. Indications for surgery were choledocholithiasis (n=18), chronic pancreatitis (n=18), iatrogenic bile duct injury (n=12), distal bile duct strictures (n=11), choledochal cyst (n=2) and other causes (n=3). Thirty-eight patients (60%) had prior surgical or endoscopic intervention. Results: Sixty hepaticojejunostomies and four choledochoduodenostomies were performed. Additional procedures during the same surgery included cholecystectomy (n=25), drainage of pseudocyst (n=4), gastroenterostomy (n=4), pancreatic biopsy (n=4), liver biopsy (n=4), cyst gastrostomy (n=2) and pancreatic necrosectomy (n=2). Postoperative complications were encountered in 12 patients – bile leak (n=2), bleeding (n=2), chest infection (n=2), MI (n =1), superficial surgical site infection (n=4) and superficial wound dehiscence (n=1). Three patients required further surgery–bile leak (n=1), bleeding (n=2). Two patients (3%) died of organ failure-one following biliary bypass for cholangitis; and one following ligation of a bleeding pseudo aneurysm. Five patients developed recurrent cholangitis requiring oral antibiotics. Conclusion: In the era of minimally invasive options, open biliary bypass remains a very effective, reliable and safe option in the management of benign conditions of the biliary system and pancreas.